The impact of suspended oyster farming on nitrogen cycling and nitrous oxide production in a sub-tropical Australian estuary. (5th June 2017) - Erler, Dirk V.; Welsh, David T.; Bennet, William W.; Meziane, Tarik; Hubas, Cédric; Nizzoli, Daniele; Ferguson, Angus J.P.
Abstract: In this study we quantified nitrate (NO3 − ) reduction (denitrification, anammox and DNRA) and N2 O production in sediments and epibiont communities associated with Sydney Rock Oyster ( Saccostrea glomerata ) farming. In sediments beneath an active suspended oyster farm, DNRA accounted for 98% of NO3 − reduction with rates of up to 169 ± 45 μmol N m −2 h −1 . Much of this DNRA was fuelled by NO3 − derived from nitrification. Reference sediments had significantly lower DNRA rates of 83.8 ± 28.2 μmol N m −2 h −1, however this constituted 96% of the sites total NO3 − reduction. Fatty acid analysis showed that sediment organic matter was more labile in the oyster impacted sediments, facilitating subtle shifts in sediment oxygen demand which increased the Fe 2+ availability with respect to the reference sediments. The difference in DNRA rate between the sites was attributed to autotrophic oxidation of soluble Fe 2+ in sediments underlying the oyster cultures. DNRA was absent in the oyster shell epibiont communities and rates of anammox and denitrification were lower than in the sediments. Production of NH4 + from the oysters and their associated epibionts was larger than DNRA and reached a rate of 206.2 μmol N m −2 h −1 . Nitrous oxide production rates were generally low compared to other aquaculture systems and the net flux of N2 O for the combined oyster cultivation system (i.e. sediments plus epibionts) was negative, i.e. there was N2 O consumption in the sediments beneath the oysters. Overall, subtropical suspended oyster farming systems favour inorganic N retention over N loss.